Molecular basis of mucopolysaccharidosis type II (Hunter syndrome): first review and classification of published IDS gene variants - Alessandra Zanetti; Francesca D’Avanzo; Rosella Tomanin (Human Genomics)
Abstract Purpose Mucopolysaccharidosis type II (MPS II) is a rare X-linked lysosomal storage disorder caused by genetic alterations in the iduronate 2-sulfatase (IDS) gene. A wide range of variants has been reported for different countries and ethnic groups. We collected, analyzed and uniformly summarized all published IDS gene variants reported in literature up to June 2023, here providing the first worldwide review and classification. Methods Data was obtained from a literature search, conducted in PubMed and Google. All data was analyzed to define the most common alleles, geographic distribution and genotype-phenotype correlation. Moreover, point variants were classified according to their pathogenicity, based on the ACMG guidelines. Results Several types of variants have been described in the IDS gene, including intrachromosomal homologous recombination occurring between the homologous regions of IDS gene and its pseudogene IDSP1. Overall, we collected 2852 individuals from 2798 families, including 24 female patients. Most families carried missense variants, followed by large deletions-insertions and complex rearrangements, small frameshift deletions/insertions and nonsense variants. Based on ACMG guidelines, 62.9% of the 779 point variants were classified as “pathogenic”, 35.4% as “likely pathogenic”, and the remaining 13 variants as having “uncertain significance”. Conclusion Data from this study confirmed that MPS II is a genetically very heterogeneous disorder, making genotype-phenotype correlation very challenging and in most cases merely unfeasible. Mutation updates are essential for the correct molecular diagnosis, genetic counseling, prenatal and preimplantation diagnosis, and disease management.